Attributes and Characteristics of Ad Spots; An Analysis of Motivation and Brand Loyalty - Bahari, Andi Faisal; Basalamah, Jafar (JURNAL MANAJEMEN BISNIS, 2020)
The reason for this paper was to decide and investigate the impact of characteristics, properties, and spots publicizing on the motivation of Madama radio audience members and how they influence brand unwaveringness. This examination is to investigate informatively and utilizing overview strategies. The investigation populace was the whole Makassar people group of Madama Radio audience members who tuned in to spots Telkomsel and clients of Telkomsel itemsThe outcomes indicated that the characteristics and nature of promotion spots have immediate and circuitous consequences for inspiration and brand steadfastness, where the advertisement spot traits have no noteworthy negative impact on inspiration, advertisement spot qualities have a critical beneficial outcome on brand unwaveringness, the nature of promotion spots has no huge negative impact on inspiration, the nature of advertisement spots has no huge constructive outcome on brand reliability, and inspiration doesn't have a huge negative impact on brand faithfulness.